Time to viral load suppression and its predictors among people living with HIV on antiretroviral therapy in Gebi Resu zone, Afar Region, Ethiopia, 2023 - Chirnet, Anteneh Tefera; Habtewold, Ephrem Mannekulih; Aman, Haji; Wakwoya, Elias Bekele; Workie, Sewnet Getaye (Frontiers in Public Health, 2024)
Objective: This study aimed to estimate the time to viral load suppression and identify its predictors among people living with HIV receiving Antiretroviral therapy (ART) in Gebi Resu zone, Afar Region, Ethiopia, 2023. Setting: The study was conducted in public health facilities in the Gebi Resu zone of Afar region. Study Design: This study is a facility based retrospective follow-up study. Study Participants: This study included 298 people living with HIV receiving ART service at selected health facilities of Gebi Resu zone. Data were collected by reviewing patient records using a structured checklist. Bivariate and multivariate Cox regression analyses were used to assess the relationship between variables and control confounders. Results: The incidence rate of viral load suppression was 9.46 per 100 person months. The median time to viral load suppression was 7.7 months with an interquartile range of 3.8 months (IQR=6.47-10.27). Patients at a clinical stages 3 and 4 (AHR=0.67, 95%CI (0.47, 0.96)), Patients who took Cotrimoxazole Prophylaxis Therapy (AHR=1.47, 95%CI (1.12, 1.92)), patients with poor drug adherence (AHR=0.40, 95%CI (0.18, 0.90)) were significantly associated with time to viral load suppression among people on antiretroviral therapy. Conclusions: The time to viral load suppression and the median time to viral load suppression among people living with HIV on ART were lower than in many developing and developed countries. Clinical stage, cotrimoxazole prophylaxis therapy, and drug adherence were significant predictors of viral load suppression.